2020
DOI: 10.1002/ajpa.24202
|View full text |Cite
|
Sign up to set email alerts
|

Increased dental fluctuating asymmetry is associated with active skeletal lesions, but not mortality hazards in the precontact Southwest United States

Abstract: Objective This study examines whether individuals with higher dental fluctuating asymmetry (DFA) are frailer than those with lower DFA, by examining whether increased DFA is associated with skeletal lesion formation. Subjects and methods 150 individuals with permanent teeth and 64 individuals with deciduous teeth. All individuals are Ancestral Puebloans from archaeological sites in modern‐day New Mexico. We estimate DFA in three ways: (a) deciduous DFA only, (b) permanent DFA only, and (c) a composite of perma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 93 publications
(144 reference statements)
0
11
0
Order By: Relevance
“…Therefore, the formation of enamel defects is a plastic response to childhood stress that theoretically should have a trade-off with later stability in growth, reflected in cranial FA (McPherson, 2021;Temple, 2019). We argue that previous research on enamel defects and FA underestimated the prevalence and frequency of early life stress because they observed LEH rather than perikymata spacing (e.g., Gawlikowska-Sroka et al, 2017;Hoover & Matsumura, 2008;Jung et al, 2016;O'Donnell & Moes, 2021a;Palubeckaité & Jankauskas, 2001). Therefore, we aim to reinvestigate the relationship between FA and early life stress by applying an altered method of measuring enamel defects that is less subject to underestimating stress.…”
Section: Objectivesmentioning
confidence: 89%
See 2 more Smart Citations
“…Therefore, the formation of enamel defects is a plastic response to childhood stress that theoretically should have a trade-off with later stability in growth, reflected in cranial FA (McPherson, 2021;Temple, 2019). We argue that previous research on enamel defects and FA underestimated the prevalence and frequency of early life stress because they observed LEH rather than perikymata spacing (e.g., Gawlikowska-Sroka et al, 2017;Hoover & Matsumura, 2008;Jung et al, 2016;O'Donnell & Moes, 2021a;Palubeckaité & Jankauskas, 2001). Therefore, we aim to reinvestigate the relationship between FA and early life stress by applying an altered method of measuring enamel defects that is less subject to underestimating stress.…”
Section: Objectivesmentioning
confidence: 89%
“…We aim to advance our understanding of the relationship between acute developmental disruption, as measured through enamel defects, and chronic instability as measured through cranial FA. Previous research on enamel defects and dental or skeletal FA have not found significant associations between them (Eriksen, 2020;Hoover et al, 2005;O'Donnell & Moes, 2021a). This is often attributed to the different experiences that these stress indicators are capturing.…”
Section: Objectivesmentioning
confidence: 96%
See 1 more Smart Citation
“…Studies have centered around such factors as endogamy, birth order, and prenatal maternal effects as predictors of dental fluctuating asymmetry (e.g., Bailit et al, 1970; Lalumière et al, 1999; Mihailidis et al, 2009; Schaefer et al, 2006). We have already discussed fluctuating asymmetry as a phenomenon beyond the genotype—in skeletal and fossil samples it is interpreted as reflecting experiences of developmental stress and examined in relation to mortality risk (e.g., Barrett et al, 2012; Gawlikowska‐Sroka et al, 2017; Milella et al, 2018; O'Donnell & Moes, 2021), with genealogical work, in many cases, affirming these expectations.…”
Section: Environmental Studiesmentioning
confidence: 94%
“…Cultural, behavioral, biological, and/or epigenetic may induce stress 7–10. ELS can manifest in a developing organism’s skeleton and dentition 11–18. Here, we examine the association between the vertebral neural canal (VNC) and other indicators of ELS and known stress events.…”
mentioning
confidence: 99%